A possibilidade de acumulação dos adicionais de insalubridade e periculosidade - Cardoso, Gerson Alves (2017)
The present study deals with the right to accumulate additional health and safety hazards, which should not be an end in itself, but a mechanism that aims to discourage the lack of initiatives of employers with the health and safety of workers, and reveals the concern With the effectiveness of the right to an adequate working environment, free from any agents that may endanger the life or health of the worker, starting from the analysis of the doctrine, jurisprudence, national and foreign legislation. In this way, undoubtedly the Labor Law has followed new directions, aiming to eradicate unemployment, keep jobs, etc., and promoting the adequate working environment essential for the dignification of the worker. However, it can be seen that preventive and corrective measures taken by employers have not always been effective in eliciting hazardous and unhealthy agents from the work environment, resulting in exposure to the danger or even sickness of the worker. Thus, recent judgments have recognized that when the measures taken to make the environment of work adequate prove unsatisfactory, it is due to the employee the right to receive, cumulatively, additional unhealthiness and dangerousness, in a true change of position of the Labor Court, And which may culminate, with the possibility of an additional insalubrity for each unhealthy agent present in the working environment